Artistic creativity as (un) realized range of national expression of Serbs on the eve of the First World War - Marković, Saša M.; Antolović, Mihael T. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
The success of the Kingdom of Serbia in the Balkan Wars 1912-1913. Not brought political stability to the country. On the contrary, certain military circles, encouraged by the success of the war felt that the time had come to national political issue resolved without hesitation. This situation has caused the election crisis in Serbia early in 1914. The Austro-Hungarian Empire Serbs were subjected to ethnic discrimination, especially since in 1912. Their conservation identity amounted to a cultural activity. It was negligible way of presenting their national feelings. On the contrary. Shortly before his assassination in Sarajevo on 28 June, 1914. Was a meeting of many Serbian choral societies in Sombor. At this event, attended by over 1000 participants who sang folk and patriotic songs. About this event could be heard in all the places where he lived for the Serbian people.